The Spatiotemporal Evolution of Storm Pulse Particulate Organic Carbon in a Low Gradient, Agriculturally Dominated Watershed - Blair, Neal E.; Bettis, Elmer Arthur; Filley, Timothy R.; Moravek, Jessie A.; Papanicolaou, A. N. Thanos; Ward, Adam S.; Wilson, Christopher G.; Zhou, Nina; Kazmierczak, Breanna; Kim, Jieun (Frontiers in Water, 2021)
Streams and rivers integrate and transport particulate organic carbon (POC) from an array of aquatic and terrestrial sources. Storm events greatly accelerate the transport of the POC. The sequences by which individual POC inputs are mobilized and transported are not well-documented but are predicted to be temporally transient and spatially dependent because of changes in forcing functions such as precipitation, discharge, and watershed morphology. In this study, the 3rd-4th order agricultural stream network, Clear Creek in Iowa, U.S.A., was sampled at a nested series of stations through storm events to determine how suspended POC changes over time and with distance downstream. Carbon and nitrogen stable isotope ratios were used to identify changes in POC. A temporal sequence of inputs was identified: in-channel algal production prior to heavy precipitation, row crop surface soils mobilized during peak precipitation, and material associated with the peak hydrograph that is hypothesized to be an integrated product from upstream. Tile drains delivered relatively 13C- and 15N-depleted particulate organic carbon that is a small contribution to the total POC inventory in the return to baseflow. The storm POC signal evolved with passage downstream, the principal transformation being the diminution of the early flush surface soil peak in response to a loss of connectivity between the hillslope and channel. Bank erosion is hypothesized to become increasingly important as the signal propagates downstream. The longitudinal evolution of the POC signal has implications for C-budgets associated with soil erosion and for interpreting the organic geochemical sedimentary record.